Diversity and distribution of the brown macroalgae (Phaeophyceae Kjellman, 1891) in cham islands, Quang Nam province, Vietnam - Van Tu, Nguyen; Trang, Le Thi; Phuong Thao, Tran Thi (Academia Journal of Biology, 2021)
The study investigated the Phaeophyceae during the year 2019 at sixteen sampling sites representative for Cham islands. Specimens were collected by scuba diving, snorkelling and walking at the upper tidal zone in both dry and rainy seasons. Twenty-five species of the Phaeophyceae identified for Cham islands from four orders, four families and eleven genera. The Sargassaceae family is the most abundant species composition, followed by Dictyotaceae, Scytosiphonaceae and Asteronemataceae family. In the six islands surveyed, Hon Lao has the highest diversity with 19 species recorded; Hon Dai, Hon Tai, Hon Kho and Hon Mo island recorded from 10 to 14 species, and the lowest diversity is at the Hon La island with 8 species. Ten species Canistrocarpus cervicornis, Dictyota spinulosa, Lobophora obscura, Lobophora variegata, Pandina minor, Sargassum bicorne, Sargassum herklotsii, Sargassum parvifolium, Turbinaria conoides, Asteronema breviarticulatum reported as new records for the marine flora of Cham islands.